2003
DOI: 10.1042/bj20021950
|View full text |Cite
|
Sign up to set email alerts
|

Daunorubicin-induced variations in gene transcription: commitment to proliferation arrest, senescence and apoptosis

Abstract: We used a human cDNA macroarray containing various oncogenes and tumour suppressor genes to assess gene expression profiles in early-passage Jurkat T lymphocytes treated with clinically relevant concentrations of the antitumour antibiotic daunorubicin. Several oncogenes and tumour suppressor genes were either up- or down-regulated depending on the daunorubicin concentration used. The expression levels of some of these genes were confirmed by semi-quantitative reverse transcriptase-PCR. We also compared the cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 41 publications
3
51
0
Order By: Relevance
“…In PC-9 cells, gefitinib treatment did not induce the up-regulation of p16 INK4A . It seems to be that induction of p21 WAF/Cip1 rather than p16 INK4A dominantly led to G 1 arrest in this cell line, as reported by Mansilla et al and te Poele et al (7,18).…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…In PC-9 cells, gefitinib treatment did not induce the up-regulation of p16 INK4A . It seems to be that induction of p21 WAF/Cip1 rather than p16 INK4A dominantly led to G 1 arrest in this cell line, as reported by Mansilla et al and te Poele et al (7,18).…”
Section: Discussionsupporting
confidence: 73%
“…Generally, induction of senescence is defined by up-regulation of CDK-inhibitors and activation of p53 (6)(7)(8). In PC-9 cells, immediate and temporal up-regulation of p21 WAF1/Cip1 followed by temporal up-regulation of p27 Kip1 was also observed with gefitinib treatment (Fig.…”
Section: Gefitinib Treatment Resulted In Immediate and Temporal Upregmentioning
confidence: 88%
See 2 more Smart Citations
“…Masquelier et al [29] demonstrated differences in the induction of apoptosis depending upon daunorubicin concentration, with higher doses correlating to more rapid caspase-3 induction and DNA fragmentation in leukemic cells. In another study, upregulation or downregulation of oncogenes and tumor suppressor genes depended on the concentration of drug used [30]. The IC 50 phenotype is thought to be representative of the cytotoxic curve for each cell line; however, no linkage peaks greater than LOD of 1.5 were found for this phenotype.…”
Section: Discussionmentioning
confidence: 99%